UJI TOKSISITAS AKUT KAPSUL BAWANG PUTIH LANANG (Allium sativum Linn) - Lusia Murtisiwi; Novena Yety Lindawati (Jurnal Ilmiah Manuntung, 2016)
Garlic (Allium sativum Linn) is evidently active against Mycobacterium tuberculosis. Garlic contains allicin that is able to inhibit the bacteria causing tuberculosis. This dried extract garlic is also qualified as content of capsules of traditional medicine, score of Total Plate Count is1.5 (required not over 10); figures of mold and yeast extract of garlic is 4.102 (required not over 104); does not contain microbial pathogens (uncontaminated with coliform bacteria, Escherichia coli, Salmonella sp, and Staphylococcus aureus); and aflatoxin is not detected (required not more than 30 CPM); the average of moisture content is 2% (required notmore than 10%). Capsule of dried extract garlic (Allium sativum Linn) meets pharmaceutical requirements for traditional medicine capsule dosage form, with9 minutes as disintegrating time (required not more than 15 minutes) and meets the uniformity of weight as required for capsule. Results of the research indicates that dried extract of garlic indose above 48.750 mg/ kg body weightto get LD50in garlic, belongs to ‘relatively harmless’. Dried extract garlic in 4 doses variations do not affect the liver functions of mice, so significant clinical toxicity symptoms that happen on entire animals test have not gained yet